Subunit rotation in Escherichia coli F(o)F(1)–ATP synthase during oxidative phosphorylation - Zhou, Yuantai (The National Academy of Sciences of the USA, 1997)
We report evidence for proton-driven subunit rotation in membrane-bound F(o)F(1)–ATP synthase during oxidative phosphorylation. A βD380C/γC87 crosslinked hybrid F(1) having epitope-tagged βD380C subunits (β(flag)) exclusively in the two noncrosslinked positions was bound to F(o) in F(1)-depleted membranes. After reduction of the β–γ crosslink, a brief exposure to conditions for ATP synthesis followed by reoxidation resulted in a significant amount of β(flag) appearing in the β–γ crosslinked product. Such a reorientation of γC87 relative to the three β subunits can only occur through subunit rotation. Rotation was inhibited when proton transport through F(o) was blocked or when ADP and P(i) were omitted. These results establish F(o)F(1) as the second example in nature where proton transport is coupled to subunit rotation.